KEMAMPUAN MENENTUKAN MAKNA GRAMATIKAL DALAM KALIMAT PADA SISWA KELAS V SEMESTER GENAP SD NEGERI 2 GUNUNG REJO PESAWARAN TAHUN PELAJARAN 2020/2021 - Riska Alfiawati; Dian Permanasari (LPPM STKIP PGRI Bandar Lampung, 2021)
This study contains the ability to determine the grammatical meaning of sentences in class V Even Semester State Elementary School 2 Gunungrejo Pesawaran Academic Year 2020/2021. Determining the grammatical meaning in the sentence under study includes several aspects, namely: 1) Paying attention to word affixation (affixation); 2) Pay attention to the repetition of language units in whole or in part (Reduplication); and 3) Pay attention to the combination of two or more words in forming words (composition). This study aims to determine and describe how the level of student ability. To achieve this goal, the author uses a qualitative descriptive method, while the data collection technique is an assignment technique. The population in this study amounted to 118 students and the research sample was set at 29 people. The sampling technique used is the Stratified proportional random sampling technique. Data analysis used the percentages.